Is there a relationship between assisted reproductive technology and maternal outcomes? A systematic review of cohort studies - Fatemeh Heshmatnia; Maryam Jafari; Leila Bozorgian; Parvin Yadollahi; Zohre Khalajinia; Marzieh Azizi (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Pregnancy with assisted reproductive technology (ART) is accompanied by fetal and maternal outcomes. Objective: This systematic review aimed to assess the relationship between ART and maternal outcomes. Materials and Methods: In this systematic review, the electronic databases, including PubMed, MEDLINE, Web of Science, Scopus, Science Direct, Cochrane Library, Google Scholar, Magiran, Irandoc, and Scientific Information Database were searched for maternal outcomes reported from 2010-2021. The Newcastle-Ottawa Scale for cohort studies was used to assess the methodological quality of studies. Results: A total of 3362 studies were identified by searching the databases. After screening abstracts and full-text reviews, 19 studies assessing the singleton pregnancy-related complications of in vitro fertilization/intracytoplasmic sperm injection were included in the study. The results demonstrated that singleton pregnancies conceived through ART had higher risks of pregnancy-related complications and adverse maternal outcomes, such as vaginal bleeding, cesarean section, hypertension induced by pregnancy, pre-eclampsia, placenta previa, and premature membrane rupture than those conceived naturally. Conclusion: In conclusion, an increased risk of adverse obstetric outcomes was observed in singleton pregnancies conceived by ART. Therefore, obstetricians should consider these pregnancies as high-risk cases and should pay special attention to their pregnancy process.